Sublingual immunotherapy not effective in house dust mite-allergic children in primary care - de Bot, Cindy M. A.; Moed, Heleen; Berger, Marjolein Y.; Röder, Esther; Hop, Wim C. J.; de Groot, Hans; de Jongste, Johan C.; Gerth van Wijk, Roy; Bindels, Patrick J. E.; van der Wouden, Johannes C. (Pediatric allergy and immunology, 2012)
To cite this article: de Bot CMA, Moed H, Berger MY, Röder E, Hop WCJ, de Groot H, de Jongste JC, van Wijk RG, Bindels PJE, van der Wouden JC. Sublingual immunotherapy not effective in house dust mite–allergic children in primary care. Pediatr Allergy Immunol 2011; Doi: 10.1111/j.1399‐3038.2011.01219.x Background:  Sublingual immunotherapy (SLIT) as a therapy for the treatment of allergic rhinitis in children might be acceptable as an alternative for subcutaneous immunotherapy. However, the efficacy of SLIT with house dust mite extract is not well established. Objective:  To investigate whether SLIT in house dust mite–allergic children recruited in primary care is effective and safe. Methods:  Children aged 6–18 years (n = 251) recruited in primary care with a house dust mite–induced allergic rhinitis received either SLIT or placebo for 2 years. Symptoms and medication use were assessed throughout the study. Primary outcome parameter was the mean total nose symptom score (scales 0–12) during the autumn of the second treatment year. Safety was assessed by recording any adverse event. Results:  Overall, the mean nose symptom score ± s.d. after 2 years of treatment showed no significant effect of SLIT (symptom score intervention group 2.26 ± 1.84 vs. placebo group, 2.02 ± 1.67; p = 0.08). There were no significant differences in secondary outcomes, nor in subgroup analyses. The number of patients reporting adverse events was comparable between both groups. Conclusions:  Sublingual immunotherapy with house dust mite allergen was not better than placebo in reducing rhinitis symptoms in house dust mite–allergic children in primary care. SLIT as administered in this study can be considered safe.